2005
DOI: 10.2136/vzj2005.0163
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Models Describing Residual NAPL Formation in the Vadose Zone

Abstract: A major shortcoming of multifluid flow simulators is the inability to predict the retention of nonaqueous phase liquid (NAPL) in the vadose zone after long drainage periods. Recently, three theoretical models—the Wipfler and van der Zee (WVDZ) model; the Van Geel and Roy (VGR) model; and the Lenhard, Oostrom, and Dane (LOD) model—have been proposed for describing residual NAPL formation. The WVDZ model assumes a critical total liquid saturation below which all NAPL becomes residual. The VGR and LOD models are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…4 for the DNAPL mass. Because the results are relatively close, it can be concluded that the 78K grid block simulations reported by Oostrom et al (2004, 2005, 2007) were sufficient for the purposes intended.…”
Section: Numerical Simulationsmentioning
confidence: 81%
See 2 more Smart Citations
“…4 for the DNAPL mass. Because the results are relatively close, it can be concluded that the 78K grid block simulations reported by Oostrom et al (2004, 2005, 2007) were sufficient for the purposes intended.…”
Section: Numerical Simulationsmentioning
confidence: 81%
“…Simulation results support a conceptual model for CCl 4 distribution where CCl 4 in the DNAPL phase migrated primarily in a vertical direction below the disposal site and where some DNAPL probably migrated across the water table into the regional aquifer. Results from Oostrom et al (2004, 2005, 2007) also show that the lower permeability Cold Creek Unit retained more DNAPL within the vadose zone than other hydrologic units during the infiltration and redistribution process. Due to the relatively high vapor pressure of the CCl 4 , the simulated vapor plumes were extensive and influenced by density‐driven advection.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…The fully implicit, integrated finite difference wateroil-air operational mode of the Subsurface Transport Over Multiple Phases code (White and Oostrom 2006) was used to conduct the 3D flow and transport simulations in domains configured based on the generalized conceptual model shown in Figure 1. The simulator has been extensively used to simulate a variety of multi-fluid systems (e.g., White et al 2004;Oostrom et al 2005). The applicable governing equations are the component mass-conservation equations for water, organic compounds, and air.…”
Section: Numerical Simulation Approach and Assumptionsmentioning
confidence: 99%